Economic Development Conditions and Their Effects on Growth Indicators Drawn from Statistics Indonesia Economic Data - Ikhsan Nendi (Journal of Applied Econometric, 2026)
Background:Understanding how economic development conditions interact to influence growth outcomes is critical for policymakers in emerging economies, especially as nations navigate post-pandemic recovery and address challenges from technological disruption and climate change.Objective:This study examines the relationship between multidimensional development conditions and growth indicators in West Java Province, Indonesia's most populous and economically diverse region. The goal is to assess how various development factors impact economic growth outcomes, such as GDP growth, employment creation, poverty reduction, and human development index outcomes.Method:The research analyzes panel data from 27 districts and cities over the period 2019–2023. Fixed-effects regression models are employed to assess the effects of infrastructure quality, human capital levels, institutional capacity, sectoral composition, and trade openness on economic performance indicators.Findings and Implications:The findings reveal that infrastructure investment significantly enhances GDP growth (coefficient 0.048, p<0.01), while human capital emerges as the strongest driver of employment growth (0.041, p<0.01) and poverty reduction (-0.095, p<0.01). These results provide evidence-based guidance for policymakers on how to prioritize development investments and create integrated strategies that leverage the synergies between infrastructure, human capital, and institutional improvements tailored to regional contexts.Conclusion:The study emphasizes that sustainable regional development requires a multidimensional approach rather than single-factor interventions. Policymakers should focus on developing integrated strategies that combine investments in infrastructure, human capital, and institutional capacity. Future research should explore spatial spillover effects and the long-term causal mechanisms that drive economic transformation.